2007
DOI: 10.1158/0008-5472.can-06-3040
|View full text |Cite
|
Sign up to set email alerts
|

Selective Down-Regulation of Glioma-Associated Oncogene 2 Inhibits the Proliferation of Hepatocellular Carcinoma Cells

Abstract: The sonic hedgehog (Shh) pathway contributes to the initiation and progression of tumors with various origins when aberrantly activated. In this study, we investigated if the Shh pathway is important for the proliferation of hepatocellular carcinoma (HCC) cells and also began to identify which components of the pathway play a pivotal role in the biology of HCC. Expression levels of components in the pathway were measured, and glioma-associated oncogene (Gli) 2 levels were found to be considerably higher in hum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
85
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 50 publications
11
85
2
Order By: Relevance
“…Previous evidence has demonstrated that the Hh signaling plays an important role in multiple tumor types. This signaling pathway is involved in and participates development, invasion and metastasis of HCC [34][35][36][37][38][39][40] . In this study, we further detected expression of Shh and Gli1 in metastasis and non-metastasis HCC liver tissues, simultaneously we used KAAD-cyc, a specific inhibitor of Hh pathway and Shh, a ligand of the Hh pathway in invasion and metastasis assays of human HCC cell line, and we confirmed the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence has demonstrated that the Hh signaling plays an important role in multiple tumor types. This signaling pathway is involved in and participates development, invasion and metastasis of HCC [34][35][36][37][38][39][40] . In this study, we further detected expression of Shh and Gli1 in metastasis and non-metastasis HCC liver tissues, simultaneously we used KAAD-cyc, a specific inhibitor of Hh pathway and Shh, a ligand of the Hh pathway in invasion and metastasis assays of human HCC cell line, and we confirmed the results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that the Hh signaling pathway is abnormally activated in human HCC [34][35][36] , and this pathway is thought to participate in the development of HCC [37][38][39] . Moreover, activation of the Hh pathway is correlated closely to invasion and metastasis of HCC [36,40] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the Hh signaling pathway may play a crucial role in tumorigenesis when reactivated in adult tissues (4)(5)(6)(7)(8). The involvement of the Hh signaling pathway in CRC has demonstrated that it is essential for human CRC growth, recurrence, metastases and stem cell expansion (9).…”
Section: Introductionmentioning
confidence: 99%
“…This results in GLI proteins activation and nuclear translocation, where they activate target gene transcription [109] . According to recent observations GLI2 is overexpressed in some HCC cell lines, and its inhibition by antisense oligonucleotides inhibits cell proliferation [110] . GLI1 overexpression occurs in a lower number of HCC cell lines and its inhibition causes lower decrease in growth rate [110] .…”
Section: Foxm1: a Pleiotropic Regulator Of Hepatocarcinogenesismentioning
confidence: 99%
“…According to recent observations GLI2 is overexpressed in some HCC cell lines, and its inhibition by antisense oligonucleotides inhibits cell proliferation [110] . GLI1 overexpression occurs in a lower number of HCC cell lines and its inhibition causes lower decrease in growth rate [110] . High levels of phosphorylated ERK1/2 (pERK1/2) and Gli1 proteins occur in neoplastic nodules and HCC induced by the resistant hepatocyte protocol in F344 rats and, at a lower extent, in BN rats (Feo et al, unpublished results).…”
Section: Foxm1: a Pleiotropic Regulator Of Hepatocarcinogenesismentioning
confidence: 99%